Determinants of healthy ageing for older people in European countries: A spatio-temporal approach - Jadwiga Suchecka; Bogusława Urbaniak (Comparative Economic Research. Central and Eastern Europe, 2016)
The European Commission (EC) has identified active and healthy ageing (AHA) as a major societal challenge mutual to European countries. This issue has increased in importance due to the progressive ageing observed in European societies, that force authorities to take initiatives for support the activity of the elderly. One of the initiatives, widely recognised is The European Innovation Partnership on Active and Healthy Ageing, which strive to enabling EU citizens to lead healthy, active and independent lives while ageing. The positive effect of actions for the AHA will be extension of the life in good health duration of EU citizens by two years by 2020. This is an important issue, as in 2013, women who have reached the age of 65 years in UE28 were facing on average 21.3 years of further life years and only 8.6 years (on average this amounted for 40.4 % of life expectancy) accounted for living in health, whereas for males, this ratio was estimated on 8.5 years in health of the anticipated further 17.9 years (47.5% of further life duration). Life expectancy in good health in older age is influenced by many different factors, i.e. cultural, social, economic and accessibility to health services and the quality of provided treatment. The last aspect is related to both the economic development of the country and the health care system management. The significant factor that has been increasingly emphasised in documentation of World Health Organisation or European Commission, concerns the investment in public and individual health. Taking into account the multivariate impact of objective and subjective factors on life expectancy in good health of elderly, the Authors decided to conduct the multidimensional comparative analysis for EU countries, including Norway, Switzerland and Iceland as well. Among the objective factors Authors distinguished: proportion of population (men and women) aged 65 years and more, economic development of the countries measured by GDP per capita, healthy life years expectancy in absolute values for males and females at 65 years, health care expenditures in PPS per inhabitant aged 65+, whereas the group of subjective characteristics consisted of: self-perceived health for people aged 65+ and self-reported unmet needs for medical services. The article aims to investigate the relationship between the length of the further life in healthy for men and women aged 65 years and selected factors in European countries in the period 2005-2012. For this purpose, following methods were used: 1/ spatial distribution of characteristics - rates of change in selected periods: 2005 and 2012, 2/ tests for dependencies using correlograms and Spearman's rank correlation coefficients, 3/ cluster analysis: on the basis of Ward's methods spatial similarities (among countries) were indicated. As the source of data the Eurostat database were used.
Keywords: 330; active aging; aging in good health; health care